Pre-Extension on-Farm Demonstration Trial of Maize in Heban Arsi and Sankura districts, southern Ethiopia - Lemma, Alemayehu; Philipos, Muluken; Mitiku, Getu; Talew, Yuel; Gizaw, Temesgen; Teshome, Derese (Journal of Science and Development, 2022)
Maize is extensively cultivated by more than 9.3 million farmers in Ethiopia. However, its productivity of the crop is low due to limitation in using and dissemination of improved maize technologies. The objective of this study was to demonstrate the performance of improved maize technologies and estimating production cost and revenue of maize technologies in large scale cultivation at Sankura and Heban Arsi districts. In this study two new maize and one locally used varieties (as a check) were used with agronomic and crop protection packages in the 2019 cropping season. At Sankura, BH- 547 gave a higher mean grain yield and showed a 10.5 and 22.7 % grain yield advantage over BH-546 and BH-540 (local check), respectively. In contrast, BH-546 produced a higher grain yield and scored a 10.2 and 1.1 % advantage over BH-547 and BH-540 in the Heban Arsi district. Similarly, participating farmers of Sankura selected BH547 based on the field performance. The BH-546 was preferred for large scale production by farmers at the Heban Arsi district. The average net benefit return of maize technology demonstration at Sankura was about 37,370.00 ETB. At Heban Arsi, the average net benefit return is estimated to be about 29,162.9 ETB. The study result revealed that the use of improved maize technology could increase maize productivity and profitability in the districts provided that farmers adopt the technology and implement following the demonstrations. Seed multiplication and distribution of BH-547 and BH-546 should be strengthened to satisfy the demand created among farmers of the districts.